Identifying Thresholds for Distance Design-based Direct Class Cohesion (D3C2) Metrics - Denny Sagita; Fajar Pradana; Bayu Priyambadha (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In the several phases of activity in developing a software system, there is design phase. This phase has a purpose to determine and ensure that a software requirement can be realized in accordance with customer needs. The quality of design must be a guarantee at this phase. One of an indicator of quality design is cohesion. Cohesion is the level of relatedness between elements in one component. A Higher value of cohesion can indicate that a component are more modular, has own resources, and less dependent on another component. More independent, components are easy to maintenance. There are many metrics to count how many values of cohesion in a component. One of metric is The Distance Design-Based Direct Class Cohesion (D3C2). But, many practitioners are unable to apply them. Because there is no threshold that can categories the value of cohesion. This study aims to determine the threshold of cohesion metric based on the class diagram. The result showed that the threshold of D3C2 metric is 0.41. 0.41 is the value that has the highest level of agreement with the design expert.